Trait Based Assessment on Teaching Writing Skill for EFL Learners - Sangar Lateef Ome; Awan Kamal Muhammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This study examines the impact of trait based assessment on teaching writing skill for EFL learners. Conducted as pre- study with one group pretest and posttest structure. The test was conducted to 11 candidates of the second trail of a language course in an institute in Erbil in 2019. Purposive sampling procedure was used in highlighting the samples. Writing test and analytical scoring rubric were the tools that have been used to gather the data. After that the data were broken down to descriptive statistics and paired sample ttest to analyze the assumption. The consequence of descriptive statistics analysis uncovered that traitbased has great impact on teaching writing skill for EFL learners as the mean score of posttest 65 was higher than mean score of pretest 42. While for hypothesis testing by using paired sample t-test at significance (2-tailed) value level, it implies that the hypothesis of this study was acknowledged. To put it differently, trait based assessment was fundamentally decisive in enhancing student's composing ability (writing skill).